Lipid-based nanoparticle formulations for small molecules and RNA drugs. (2nd November 2019) - Ickenstein, Ludger M.; Garidel, Patrick
ABSTRACT: Introduction : Liposomes and lipid-based nanoparticles (LNPs) effectively deliver cargo molecules to specific tissues, cells, and cellular compartments. Patients benefit from these nanoparticle formulations by altered pharmacokinetic properties, higher efficacy, or reduced side effects. While liposomes are an established delivery option for small molecules, Onpattro® (Sanofi Genzyme, Cambridge, MA) is the first commercially available LNP formulation of a small interfering ribonucleic acid (siRNA). Areas covered : This review article summarizes key features of liposomal formulations for small molecule drugs and LNP formulations for RNA therapeutics. We describe liposomal formulations that are commercially available or in late-stage clinical development and the most promising LNP formulations for ASOs, siRNAs, saRNA, and mRNA therapeutics. Expert opinion : Similar to liposomes, LNPs for RNA therapeutics have matured but still possess a niche application status. RNA therapeutics, however, bear an immense hope for difficult to treat diseases and fuel the imagination for further applications of RNA drugs. LNPs face similar challenges as liposomes including limitations in biodistribution, the risk to provoke immune responses, and other toxicities. However, since properties of RNA molecules within the same group are very similar, the entire class of therapeutic molecules would benefit from improvements in a few key parameters of the delivery technology.